2008
DOI: 10.3201/eid1412.080499
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Molecular Subtyping ofVibrio vulnificusIllnesses, Israel

Abstract: The genetically distinct biotype 3 has penetrated Israeli freshwaters and is causing severe illness in persons who handle tilapia or carp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 32 publications
1
43
0
Order By: Relevance
“…6A). However, BT3 infections are not strongly correlated with underlying infection or high iron content, as 45% of patients have no predisposing conditions (15). In mice not treated with iron dextran, mice also succumbed to infection with BAA87rif in a dose-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…6A). However, BT3 infections are not strongly correlated with underlying infection or high iron content, as 45% of patients have no predisposing conditions (15). In mice not treated with iron dextran, mice also succumbed to infection with BAA87rif in a dose-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…From 1996 to 1999, changes in marketing practices to allow vendors to sell live fish in Israel led to an outbreak of a new lineage of V. vulnificus, resulting in a large number of wound infections associated with the handling and preparation of tilapia and carp (14). These BT3 strains continue to be present in fish ponds and the Sea of Galilee and have caused nearly 200 infections with 10% mortality from 1996 to 2008 (15).…”
mentioning
confidence: 99%
“…Despite the abundance of diverse environmental populations of V. vulnificus in Israel (Broza et al, 2009(Broza et al, , 2012, nearly all microbiologically confirmed infections in Israel were caused by the same biotype 3 (sequence type 8 by MLST) (Bisharat et al, 1999(Bisharat et al, , 2005Broza et al, 2009;Zaidenstein et al, 2008). These observations emphasized the virulent potential of biotype 3.…”
Section: Introductionmentioning
confidence: 90%
“…One hundred twelve patients required a single drug (47 with ampicillin-clavulanate, 27 doxycycline, six ceftriaxone). The rest required combined treatment [1].…”
Section: Discussionmentioning
confidence: 99%
“…This is more prevalent in patients with chronic liver disease as well as other immune-compromising states, and is mainly induced by direct injury from the fish backbone while purchasing, cleaning or handling live fish [1].…”
Section: Introductionmentioning
confidence: 99%